2015
DOI: 10.1002/qj.2590
|View full text |Cite
|
Sign up to set email alerts
|

Energy‐conserving finite‐difference schemes for quasi‐hydrostatic equations

Abstract: †The contributions of Thomas Melvin were written in the course of his employment at the Met Office, UK and are published with the permission of the Controller of HMSO and the Queen's Printer for Scotland.The pressure-based hydrostatic primitive equations model LMD-Z is extended to solve the quasi-hydrostatic deep-atmosphere as well as the non-traditional shallow-atmosphere equations (with a complete Coriolis force representation).The continuous equations are first derived in their curl form using Eulerian hori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…As discussed in Mayne et al (2014b) the physical justification for the traditional approximation is relatively weak, and concerns have been raised over its validity for thick atmospheres (Tokano 2013;Mayne et al 2014b), and terrestrial planets (Gerkema et al 2008;Tort et al 2015). Also as discussed the condition w v tan φ indicates whether the terms omitted by this approximation are negligible or not.…”
Section: Traditional Approximationmentioning
confidence: 99%
See 3 more Smart Citations
“…As discussed in Mayne et al (2014b) the physical justification for the traditional approximation is relatively weak, and concerns have been raised over its validity for thick atmospheres (Tokano 2013;Mayne et al 2014b), and terrestrial planets (Gerkema et al 2008;Tort et al 2015). Also as discussed the condition w v tan φ indicates whether the terms omitted by this approximation are negligible or not.…”
Section: Traditional Approximationmentioning
confidence: 99%
“…In addition Tort et al (2015) have shown that the traditional approximation becomes increasingly less valid as, in their case, Ω is increased, yet ΩR p remains constant, for the terrestrial regime. If ΩR p is constant, Eqn (22) is clearly constant for a given φ. Eqn (17) (22) and (17) also make interesting predictions for the atmospheric interaction with condensates.…”
Section: Traditional Approximationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a similar Z grid scheme based on a Helmholtz decomposition of the momentum instead of the wind, which does conserve both total energy and potential enstrophy, was developed by Salmon (2005Salmon ( , 2007 using techniques from Hamiltonian mechanics (specifically, Nambu brackets). The idea of using Hamiltonian mechanics to derive conservative models for atmospheric dynamical cores has seen a great deal of interest and progress in the past 10 years (see Gassmann and Herzog, 2008;Gassmann, 2013;Sommer and Névir, 2009;Nevir and Sommer, 2009;Dubos and Tort, 2014;Dubos et al, 2015;Tort et al, 2015;Salmon, 1988;Shepherd, 2003). With the recent development of Hamiltonian formulations for essentially all of the equation sets and vertical coordinates used in atmospheric dynamics, it seems likely that this approach will continue to be employed in the future.…”
Section: Introductionmentioning
confidence: 99%